The Influence of Leadership Style and Motivation on Employee Performance in Bhagasasi Bekasi Regional Public Companies - Hanafi, Ali Al; Arifin, Antoni Ludfi (Dinasti International Journal of Management Science, 2025)
This research aims to determine the influence of leadership style and motivation on employee performance at the Bhagasasi Bekasi Regional Public Company. The method used is a quantitative method with a survey approach. Data was collected through a questionnaire distributed to employees working at the company. Data analysis was carried out using multiple linear regression to determine the direct influence of leadership style and motivation on employee performance. The results of this research indicate that both leadership style and motivation significantly influence employee performance at the Bhagasasi Bekasi Regional Public Company. This research contributes to the development of human resource management theory, especially in improving employee performance in the public sector.